Ultimate failure load analysis of cross-laminated timber panels subjected to in-plane compression. (January 2023) - Heinisuo, Markku; Pajunen, Sami; Aspila, Aku
Abstract: Cross-laminated timber (CLT) panels have proved their efficiency as vertical and horizontal load-carrying structures, and their design methods for serviceability and ultimate limit states are well defined. However, there is a lack of more general and versatile analytical methods for the ultimate load carrying capacity determination of CLT structures. In this paper, the classical layered beam theory is adopted for the ultimate failure load estimation of axially compressed CLT panels. The proposed method retains its accuracy both with an asymmetric layer setup and when the number of CLT layers exceeds five. The presented method is validated by adopting experimental test data from two test series produced by other researchers.